Identifying regional labor demand shocks using sign restrictions - Falko Juessen; Ludger Linnemann (Institute for the Study of Labor (IZA), 2012)
We propose using sign restrictions to identify regional labor demand shocks in a panel VAR of US federal states. Observed migration responds significantly, but less persistently than the residual-based migration measure constructed by Blanchard and Katz (1992).
Keywords: E24; R11; C33; C32; 330; regional labor markets; migration; panel VAR; sign restrictions; Arbeitsnachfrage; Schock; Regionaler Arbeitsmarkt; Binnenwanderung; Schätzung; USA